First osteological evidence of severed hands in Ancient Egypt - Julia Gresky; Manfred Bietak; Emmanuele Petiti; Christiane Scheffler; Michael Schultz (Scientific Reports, 2023)
Abstract For the first time, the severed right hands of 12 individuals have been analysed osteologically. The hands were deposited in three pits within a courtyard in front of the throne room of a 15th Dynasty (c.1640–1530 BC) Hyksos palace at Avaris/Tell el-Dab‘a in north-eastern Egypt. Although this kind of practice is known from tomb or temple inscriptions and reliefs from the New Kingdom onwards, this is the first time that physical evidence has been used to learn more about the procedure and the individuals whose hands were taken. Here, we show that the right hands belonged to at least 12 adults, 11 males, and possibly one female. It is unclear if the hands were taken from dead or living individuals. After removing any attached parts of the forearm, the hands were placed in the ground with wide-splayed fingers, mainly on their palmar sides. The osteological analysis not only supports the archaeological interpretation of this evidence but also adds more detail regarding trophy-taking practices in Ancient Egypt.